PHOTOCATALYTIC ACTIVITY OF REDUCED GRAPHENE OXIDE/ COPPER OXIDE (RGO/CUO) IN DEGRADATION OF ORGANIC POLLUTANT (RHODAMINE B) - Latifah (NIM : 10211016), Hidayatul
Graphene is an allotrope of carbon in the form of a two – dimensional sheet which has an interesting properties such as a high electrical conductivity and large specific surface area. Copper oxide (CuO) is a semiconductor material with high photocatalytic activity, nontoxic and also has a facile method. In previous study, it has been reported that these materials can be used as photoctalyst for degradation of organic dye. In this study, the composite of rGO/CuO has been synthesized in varying CuO concentration from 0.5 until 5 wt% through a modified Marcano. Crystalization of CuO and reduction of graphene oxide into reduced graphene oxide were conducted simultaneously with hydrazine hydrate as reduction agent asissted by microwave radiation. The resulted composites were characterized by FTIR, SEM, EDS and XRD. The FTIR results shows the presence of C=C, C–O and Cu-O bondings which indicated the formation of rGO and CuO. In addition, the formation of CuO on the rGO was also indicated by SEM images. Based on SEM images, the irregular shapes which are supposed to be CuO, were obviously observed on the thin sheets which is supposed to be rGO layers. Moreover, the EDS mapping of rGO/CuO 1 wt% shows that sample consist of C, O and Cu atoms with atomic ratio 95:4:1. The XRD results show that not only the characteristic peaks of CuO was observed, but also Cu2O and Cu crystall which might be spountaneously generated through a reduction process under microwave radiation. The photocatalytic performace of this composite will be examined on the organic pollutant degradation (Rhodamin B).